2017
DOI: 10.1007/s13197-017-2766-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage environment, maturity stage and pre-storage disinfection treatments on tomato fruit quality during winter in KwaZulu-Natal, South Africa

Abstract: The aim of this study was to explore influence of evaporative cooling (EC), pre-storage disinfection treatments and maturity stage at harvest on postharvest quality of tomato fruit. The tomato samples ( Mill. cv. Nemonetta) were harvested, stored for 28 days and data were collected every seven days. The pH, total titratable acidity (TTA), total soluble solids (TSS), firmness, colour, weight loss (PWL) and marketability percentage were analysed. The temperature difference between ambient storage and EC at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
8
32
0
Order By: Relevance
“…The significant differences in temperature in relation to the position of sensors in the storage chamber could influence the quality of FV stored inside the IAC þ EC storage chamber. The results observed in this study are in conformity with [29] who indicated that the temperature variations between sensors at the entry and exit of the storage chamber was about 2 C. Determining the ventilation rate to maintain a uniform air distribution in the storage chamber is important as it ensures that an optimal storage environment exists to maintain the physiological condition of fresh produce [30]. The average temperature distribution inside the storage chamber varied from 16.2 C to 16.9 C implying that the IAC þ EC provided optimum temperature condition for the storage of most of the tropical and sub-tropical FV.…”
Section: Variation Of Temperaturesupporting
confidence: 91%
See 2 more Smart Citations
“…The significant differences in temperature in relation to the position of sensors in the storage chamber could influence the quality of FV stored inside the IAC þ EC storage chamber. The results observed in this study are in conformity with [29] who indicated that the temperature variations between sensors at the entry and exit of the storage chamber was about 2 C. Determining the ventilation rate to maintain a uniform air distribution in the storage chamber is important as it ensures that an optimal storage environment exists to maintain the physiological condition of fresh produce [30]. The average temperature distribution inside the storage chamber varied from 16.2 C to 16.9 C implying that the IAC þ EC provided optimum temperature condition for the storage of most of the tropical and sub-tropical FV.…”
Section: Variation Of Temperaturesupporting
confidence: 91%
“…The highest RH of 93.8% occurred near the inlet to the storage chamber while the lowest value was at the exhaust end (89.6%). The results observed in this study show similar trends with [29] who indicated that the RH variations between sensors at the entry and exit of the storage chamber were about 12% C. The RH value of 93.8% was the maximum possible level of saturation of air by humidification for IAC þ EC system as 100% RH is not achievable in a direct EC experiment [32]. To achieve 100% will require a cooling pad with a 100% efficiency and the contact time between air and water should be long enough to allow for 100% heat and mass transfer, which in reality does not happen [33].…”
Section: Variation Of Relative Humiditysupporting
confidence: 89%
See 1 more Smart Citation
“…This study then considers adoption of an indirect air-cooling system combined with evaporative cooling (IAC+EC) which can work both in hot and dry climates and hot and humid areas through incorporation of an indirect heat exchanger (IHE). Tolesa and Workneh (2017) investigated the effect of IAC+EC on the quality of stored tomato fruit over a 30day period compared to ambient conditions. The tomatoes stored under IAC+EC showed higher firmness and hue angle, maintained lower concentration of sugars, had lower physiological weight loss and improved shelflife and marketability as compared to ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is an important environmental factor which is known to decrease and or increase processes occurring in a produce depending on the temperature it is exposed to. Hence, Tolesa and Workneh (2017) suggested that the correct way of preventing postharvest losses caused by the use of inappropriate temperatures from affecting tomatoes chemical properties is exposing the produce to its optimum cooling temperature requirements during postharvest. According to Munoz et al.…”
Section: Introductionmentioning
confidence: 99%